CULTUROLOGICAL APPROACH IN THE FORMATION CONTENTS OF THE PEDAGOGICAL TRAINING OF THE FUTURE TEACHER AT A CLASSICAL UNIVERSITY - Shtelmakh, H.B. (Pedagogy of Higher and Secondary Education, 2003)
No abstract.